2007
DOI: 10.1007/s10832-007-9374-1
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric coefficients of PMN-0.29PT single crystals in the temperature range of phase transitions

Abstract: The temperature dependencies of piezoelectric coefficients d 33 and d 31 for Pb(Mg 1/3 Nb 2/3 )O 3 -0.29PbTiO 3 multi-domain single crystals, poled in [001]-direction, were investigated. The two samples had x-and y-axes identical with crystallographic [100] and [010] directions respectively, and the second two samples with [−110] and [110]directions. The laser interferometry method was used for the piezoelectrically induced displacement measurement. Piezoelectric coefficients were similar for all samples at ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Sulc and colleagues (Ref. 13) report that k 31 remains constant until the phase transition temperature, and then decreases 35%. Upon cooling, k 31 does not return to its original value until cooled to room temperature.…”
Section: Temperature-testing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulc and colleagues (Ref. 13) report that k 31 remains constant until the phase transition temperature, and then decreases 35%. Upon cooling, k 31 does not return to its original value until cooled to room temperature.…”
Section: Temperature-testing Resultsmentioning
confidence: 99%
“…As temperature increases, the magnitude of d 31 (charge coefficient) increases (Ref. 13). However, it is shown that the electromechanical coupling factor, k 31 , for PMN-PT material remains stable with temperature before its phase transition (Ref.…”
Section: Temperature-testing Resultsmentioning
confidence: 99%
“…The value of d 33 * increased apparently with the rising of temperature and reached the maximum at 110 °C (around FE R ‐FE M phase transition), and then decreased drastically with the further increase in temperature and nearly disappeared above the T m . The considerable improvement of piezoelectric properties around the ferroelectric phase transition temperature was also observed in PMN‐PT and PZN‐PT single crystals, which can be attributed to the phase instability induced by ferroelectric phase transition, the easy mobility of domain walls, the discontinuity in polarization across phase boundaries, etc . In order to deeply understand the relationships between structure and properties, it is necessary to further study the phase transition characteristics of Mn‐0.15PIN‐0.55PMN‐0.30PT crystal.…”
Section: Resultsmentioning
confidence: 99%
“…The considerable improvement of piezoelectric properties around the ferroelectric phase transition temperature was also observed in PMN-PT and PZN-PT single crystals, which can be attributed to the phase instability induced by ferroelectric phase transition, the easy mobility of domain walls, the discontinuity in polarization across phase boundaries, etc. [24] In order to deeply understand the relationships between structure and properties, it is necessary to further study the phase transition characteristics of Mn-0.15PIN-0.55PMN-0.30PT crystal. Raman spectroscopy is proved to be an effective tool to study the local structure and phase transitions of the relaxor-PT crystals.…”
Section: Resultsmentioning
confidence: 99%